대퇴탈장 수술 전후의 진단 일치율과 진단의 정확도에 영향을 미치는 요인 - 유호길(Ho-gil Yoo); 이광만(Kwang-man Lee); 최운정(Un-jong Choi) (Annals of surgical treatment and research, 2009)
Purpose: Misdiagnosis is frequent in femoral hernia as inguinal hernia. The aims of this study were to examine the diagnostic concordance and to define the factors having influence on the correct diagnosis of femoral hernia. Methods: Thirty-two patients who underwent femoral hernia operations were analyzed retrospectively. Results: The mean age of the study subjects was 65.8±15.5 (36∼97) and the female to male ratio was 5.4：1. The mean body mass index (BMI) was 19.8 kg/m² (14.6∼26.9 kg/m²). Twelve patients (37.5%) showed pre- and post-operative diagnostic concordance and 20 patients (62.5%) did not. Among the 20 misdiagnosed cases, 16 cases were misdiagnosed as inguinal hernia, 2 cases as lipoma, and 1 case as lymphadenopathy. The factors related to the correct diagnosis of femoral hernias were associated with groin mass (96.9%, 31/32: 23 painless and 8 painful), size fluctuation of mass (cyclic wax and wane pattern) (84.4%, 27/32), long duration of mass (over 1 month) (75.0%, 24/32), femoral venous compression CT findings (63.6%, 14/22), and positive ultrasonographic findings (42.1%, 8/19). Emergency operation was done in 12 cases (37.5%). Incarceration was found in 23 cases (71.9%) and most of the incarcerated organs were omental fat (11 cases) and small bowel (10 cases). Bowel resection was done in 4 cases and 2 patients combined inguinal hernia. Conclusion: Through the careful taking of medical history and physical examination, physicians can achieve the correct diagnosis and can also decrease the frequency of emergency operations and their related complications. Purpose: Misdiagnosis is frequent in femoral hernia as inguinal hernia. The aims of this study were to examine the diagnostic concordance and to define the factors having influence on the correct diagnosis of femoral hernia. Methods: Thirty-two patients who underwent femoral hernia operations were analyzed retrospectively. Results: The mean age of the study subjects was 65.8±15.5 (36∼97) and the female to male ratio was 5.4：1. The mean body mass index (BMI) was 19.8 kg/m² (14.6∼26.9 kg/m²). Twelve patients (37.5%) showed pre- and post-operative diagnostic concordance and 20 patients (62.5%) did not. Among the 20 misdiagnosed cases, 16 cases were misdiagnosed as inguinal hernia, 2 cases as lipoma, and 1 case as lymphadenopathy. The factors related to the correct diagnosis of femoral hernias were associated with groin mass (96.9%, 31/32: 23 painless and 8 painful), size fluctuation of mass (cyclic wax and wane pattern) (84.4%, 27/32), long duration of mass (over 1 month) (75.0%, 24/32), femoral venous compression CT findings (63.6%, 14/22), and positive ultrasonographic findings (42.1%, 8/19). Emergency operation was done in 12 cases (37.5%). Incarceration was found in 23 cases (71.9%) and most of the incarcerated organs were omental fat (11 cases) and small bowel (10 cases). Bowel resection was done in 4 cases and 2 patients combined inguinal hernia. Conclusion: Through the careful taking of medical history and physical examination, physicians can achieve the correct diagnosis and can also decrease the frequency of emergency operations and their related complications. KCI Citation Count: 2